LOGICO-SEMANTIC RELATION IN SRI MULYANI INDRAWATI’S SPEECH - Muliani; Juli Rachmadani Hasibuan (State University of Medan, 2015)
This study deals with logico-semantic relation in Sri Mulyani Indrawati’s speech.The objectives of this study were to describe the logico-semantic type and howlogico-semantic used in the speech. This study was conducted by usingdescriptive qualitative. The data of this study were clause complexes found in theSri Mulyani’s speech. There were 142 clause complexes as the sample. Based onthe analysis, it was found that only eight of ten types of logico-semantic wereused in Sri Mulyani’s speech. The types that were not found are ParatacticLocution and Paratactic Idea. The most occurrence type of logico-semantic wasParatactic Extension (26.76%). Then followed by Hypotactic Enhancement(23.23%), Hypotactic Elaboration (21.12%), Hypotactic Extension (19.01%),Paratactic Elaboration (4.92%), Paratactic Enhancement (2.81%), Hypotactic Idea(1.41%), and Hypotactic Locution (0.71%). For the use of paratactic extension asthe most used by Sri Mulyani indicates that she presented her ideas by adding,varying, and replacing the messages by using the conjunctions and, but, and or.